Synthesis and Characterization of Highly Intercalated Graphite Bisulfate - Salvatore, Marcella (Nanoscale Res Lett, 2017)
Different chemical formulations for the synthesis of highly intercalated graphite bisulfate have been tested. In particular, nitric acid, potassium nitrate, potassium dichromate, potassium permanganate, sodium periodate, sodium chlorate, and hydrogen peroxide have been used in this synthesis scheme as the auxiliary reagent (oxidizing agent). In order to evaluate the presence of delamination, and pre-expansion phenomena, and the achieved intercalation degree in the prepared samples, the obtained graphite intercalation compounds have been characterized by scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDS), X-ray powder diffraction (XRD), infrared spectroscopy (FT-IR), micro-Raman spectroscopy (μ-RS), and thermal analysis (TGA). Delamination and pre-expansion phenomena were observed only for nitric acid, sodium chlorate, and hydrogen peroxide, while the presence of strong oxidizers (KMnO(4), K(2)Cr(2)O(7)) led to stable graphite intercalation compounds. The largest content of intercalated bisulfate is achieved in the intercalated compounds obtained from NaIO(4) and NaClO(3).